Case Report: Hemodynamic Instability Following Severe Metoprolol and Imipramine Intoxication Successfully Treated With Intravenous Fat Emulsion. (January 2016) - van den Berg, Maarten Jan Willem; Bosch, Frank H.
Abstract : We present the case of a 22-year-old patient who was successfully treated with intravenous fat emulsion for severe and refractory cardiac depression after an overdose with a tricyclic antidepressant and beta-blocker.